Empire and the Bomb : How the U.S. Uses Nuclear Weapons to Dominate the World - Gerson, Joseph; Preface By Walden Bello (London Pluto Press, 2007)
As Americans, we need to face up to our own reliance on nuclear intimidation. This is an important book for Americans of all political stripes to read.' Cynthia Enloe, author of The Curious Feminist: Searching for Women in a New Age of Empire "At a time when nuclear weapons are increasingly in the political spotlight, this book is essential reading . . . Joseph Gerson has provided a work of the utmost importance: a key to understanding - and challenging - US global domination and its nuclear core." Kate Hudson, Chair, Campaign for Nuclear Disarmament "Brilliant. I have not read a more important book in many years. Gerson has uncovered the radioactive vein in our secret foreign policy. . . . Gerson's work helps us understand why the likelihood of nuclear war is greater now than before the fall of the Berlin Wall. A terrific book." Daniel Ellsberg, former senior Pentagon official and co-author of The Pentagon Papers The United States is the only country to have dropped the atomic bomb. Since the A-bombings of Hiroshima and Nagasaki, every U.S. president has threatened nuclear war. This concise history shows how the U.S. has used nuclear weapons to bolster its imperial ambitions. Leading nuclear specialist and peace campaigner Joseph Gerson explains why atomic weapons were first built and used -- and how the U.S. uses them today to preserve its global empire. Gerson reveals how and why the U.S. made more than twenty threats of nuclear attack during the Cold War -- against Russia, China, Vietnam, and the Middle East. He shows how such theats continued under Presidents Bush and Clinton, and George W. Bush. The book concludes with an appeal for nuclear weapons abolition and an overview of the history of the anti-nuclear movement. Drawing from a wide range of sources, this fascinating and timely account shows how the U.S. has used nuclear weapons to dominate the world.
Include Notes, Index and Bibliography.
A concise history of how the US has used nuclear weapons to dominate the world.
Keywords: Military Policy -- Nuclear Disarmament